Therapeutics effects of aqueous extract Cynodon Dactylon on the mice model ulcerative colitis - Abolfazl Abbaszadeh; Shahsanam Gheibi; Leila Zarei; Hadi Esmaeili Gouvarchin ghaleh * (Lorestan University of Medical Sciences, 2019)
Background and Aim: Cynodon dactylon (C. dactylon) has long been examined for its anti-inflammatory properties. A type of Inflammatory Bowel Disease (IBD) is Ulcerative Colitis (UC). This study investigated the impacts of C. dactylon on the inflammatory mediators of UC induced by acetic acid in Wistar rats. Materials & Methods: The experiment was conducted on 50 male Wistar rats grouped into five equal individuals. Excluding Group I (negative control), acetic acid was used to induce UC in the rats. The treatments received different doses of C. dactylon extract, namely Group II (1 mL of 200 mg/kg orally per day, Group III (1 mL of 200 mg/kg as intra-colonic), Group IV (1 mL of intra-colonic 10 mg/kg Mesalazine), and Group V (1 mL of normal saline) as positive control. The whole treatments lasted for 10 successive days. At completion of the study, intestinal tissue and blood samples were taken from sacrificed rats. Measured parameters were inflammatory mediators, myeloperoxidase (MPO), superoxide dismutase (SOD), glutathione peroxidase (GPx), and activities of cytokines TNF-α and IL-6. Results: A more remedial advantage of C. dactylon extract in two forms of trans-rectal and oral administration was observed on damaged colonic tissue induced by acetic acid with reduced activities of MPO, SOD and GPx. Amounts of TNF-α and IL-6All were lowered by all treatments. Mesalazine and C. dactylon extract were not significantly different in terms of gross damages. Conclusions: Our observations indicate that C. dactylon extract with anti-colitis property can be regarded as an appropriate candidate and a natural source of current medications.